2010
DOI: 10.1111/j.1749-6632.2010.05505.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the evolution of proglucagon‐derived peptides and receptors in fish and amphibians

Abstract: Glucagon and the glucagon-like peptides (GLP-1 and GLP-2) share a common evolutionary origin and are triplication products of an ancestral glucagon exon. In mammals, a standard scenario is found where only a single proglucagon-derived peptide set exists. However, fish and amphibians have either multiple proglucagon genes or exons that are likely resultant of duplication events. Through phylogenetic analysis and examination of their respective functions, the proglucagon ligand-receptor pairs are believed to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
(164 reference statements)
2
27
0
Order By: Relevance
“…The zebrafish GIPR has been shown to functionally bind GIP. We, and others, were unable to identify a Gipr in the other fish genomes (Table 1) [28,35,36] and similar results have been reported for the Gip gene, where Gip sequences have only been found in the zebrafish genome and salmon cDNA [18,34,36]. Intriguingly, no near full‐length Gipr could be identified in any of the four available bird genomes (Table 1).…”
Section: Identification Of Diverse Vertebrate Glucagon Receptor‐like supporting
confidence: 80%
See 3 more Smart Citations
“…The zebrafish GIPR has been shown to functionally bind GIP. We, and others, were unable to identify a Gipr in the other fish genomes (Table 1) [28,35,36] and similar results have been reported for the Gip gene, where Gip sequences have only been found in the zebrafish genome and salmon cDNA [18,34,36]. Intriguingly, no near full‐length Gipr could be identified in any of the four available bird genomes (Table 1).…”
Section: Identification Of Diverse Vertebrate Glucagon Receptor‐like supporting
confidence: 80%
“…It has been suggested recently that fish genomes do contain a gene orthologous to mammalian Glp1r [28]. This conclusion was drawn from an analysis of a more complete set of receptor genes from diverse vertebrate species and was strengthened by the claim that the putative fish Glp1r was in a genomic neighbourhood that was conserved with amphibians and was linked to genes that are on the same chromosome that encodes mouse Glp1r [28].…”
Section: Glucagon Receptor Gene Subfamilymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, due to genome duplication, fish have duplicate proglucagon genes that generate multiple mRNA transcripts (Irwin and Wong, 1995;Zhou and Irwin, 2004). Proglucagon or PGDPs have been reported in several groups of fish (Ng et al, 2010). In fish, evidence has shown that GLP-1 and other PGDPs may affect feeding and energy homeostasis (Mommsen and Moon, 1989;Mojsov, 2000;Silverstein et al, 2001;Polakof et al, 2011).…”
Section: Introductionmentioning
confidence: 93%